Making Elchem Card Game Media on The Concept Of Effective Nuclear Charge and Slater Rules - Tya Hikmatul Aliyah; Ferli Septi Irwansyah; Imelda Helsy (Gunung Djati Conference Series, 2022)
The Research based on the necessity of attractive media for effective nuclear charge and Slater rules learning. Accordingly, in this research Elchem Card Game learning media was made, which was a card game with flow of use inspired by Intermolecular Forces Game. By using Design Based Research method, this research intended to result the product and to analyze the result of product’s validation test and trial test. Validation test of Elchem Card Game results an average calculation 0,85 in learning aspect, 0,86 in concept substance aspect, 0,86 in language aspect, and 0,86 in media visual aspect. As for trial test shows that Elchem Card Game is very feasible with percentage in learning aspect is 94%, in concept substance aspect is 100%, in language aspect is 94%, and in media visual aspect is 87%. Therefore, it can be concluded that Elchem Card Game can be used as learning media in effective nuclear charge and Slater rules concepts